TRPM7/RPSA Complex Regulates Pancreatic Cancer Cell Migration - Lefebvre, Thibaut; Rybarczyk, Pierre; Bretaudeau, Clara; Vanlaeys, Alison; Cousin, Rémi; Brassart-Pasco, Sylvie; Chatelain, Denis; Dhennin-Duthille, Isabelle; Ouadid-Ahidouch, Halima; Brassart, Bertrand; Gautier, Mathieu (Frontiers in Cell and Developmental Biology, 2020)
Pancreatic ductal adenocarcinoma (PDAC) is a malignancy with a very poor prognosis due to highly metastatic profile. Cell migration is an essential step of the metastatic cascade allowing cancer cells to spread toward target tissues. Recent studies strongly suggest that bioactive elastin peptides, also named elastokines or elastin-derived peptides (EDPs), are released in the extracellular microenvironment during tumoral remodeling of the stroma. EDPs stimulate cancer cell migration by interacting with their membrane receptor, Ribosomal Protein SA (RPSA). Others membrane proteins like ion channels are also involved in cancer cell migration. It has been recently shown that the Transient Receptor Potential Melastatinrelated 7 (TRPM7) channel regulates PDAC cell migration and invasion. The objective of this work was to study the effect of EDPs on TRPM7 channel in human pancreatic cancer cells.We showed that EDPs promote MIA PaCa-2 cell migration by using Boyden chamber assay. Cells transfected with a siRNA targeting TRPM7 were not able to migrate in response to EDPs indicating that TRPM7 regulated cell migration induced by these peptides. Moreover, EDPs were able to stimulate TRPM7 currents recorded by Patch-Clamp. Finally, we showed that TRPM7 channels and RPSA receptors are colocalized at the plasma membrane of human pancreatic cancer cells.Taken together, our data suggest that TRPM7/RPSA complex regulated human pancreatic cancer cell migration. This complex may be a promising therapeutic target in PDAC.